Biomarkers and mechanisms of tolerance induction in food allergic patients drive new therapeutic approaches - Baloh, Carolyn H.; Huffaker, Michelle F.; Laidlaw, Tanya (Frontiers in Immunology, 2022)
Immunotherapy for food-allergic patients has been effective in inducing desensitization in some populations, but long-term tolerance has remained an elusive target. A challenge facing our field is how to differentiate immune markers that are impacted by immunotherapy from those that are critical biomarkers of tolerance. Data from recent clinical trials have identified several biomarkers and mechanisms for achieving tolerance. These biomarkers include younger age, lower food-specific IgE, lower food component-specific IgE, specific linear epitope profiles, and subsets of food-specific CD4+ T cells. Additional biomarkers under investigation for their relevance in tolerance induction include TCR repertoires, gastrointestinal and skin microbiome, and local tissue immunity. This mini-review highlights recent advances in understanding biomarkers and mechanisms of tolerance induction in food immunotherapy and how these are influencing clinical trial development.